Sosyo-kültürel açıdan İstanbul'da ermeni toplumu (XIX. Yüzyıl) - Külekçi, Cahit (My University, 2009)
Sosyo-Kültürel Açıdan İstanbul’da Ermeni Toplumu (XIX. Yüzyıl) Osmanlı Devleti’nin kurulduğu yıllarda Ermeniler küçük krallıklar ve topluluklar halinde yaşıyorlardı. Ermeniler bu yıllarda Bizans, Selçuklu ve diğer güçlü devletlerin hakimiyetleri altında bulunan Çukurova, Doğu Anadolu ve Kafkasya bölgelerinde ikâmet etmekteydiler. Osman Gazi tarafından devletin başkenti 1324 yılında Bursa olduktan sonra özellikle Kütahya ve civarında bulunan Ermeniler Bursa’ya, İstanbul’un 1453 yılında fethedilmesinden sonra da İstanbul’a nakledilmişlerdir. Ermenileri Bursa’dan İstanbul’a nakleden Fatih Sultan Mehmet, Hovakim’i Ermeni patriği olarak atamış ve Bizanslıların hakimiyeti altında bulunan Ermeni patrikliği de bağımsızlığına kavuşmuştur. Ermeniler Osmanlı Devleti’nde her zaman birinci sınıf vatandaş olarak muamele görmüşler ve devletin hem bürokratik hem de ekonomik alanında devlete hizmet vermişlerdir. Diğer gayr-ı Müslimler gibi Ermeniler de Osmanlı Devleti içerisinde rahatça ve özgürce yaşamışlar, ülke yönetminin önemli kademelerinde görev almışlardır. From The Social-Cultural Point of View Armenian Society in Istanbul (XIX. Century) In the first years of the Ottoman Empire, Armenians were scattered as small princedoms and emirates. They were living as subjects of Iran, Byzantine Empire, Georgian and Seldjukian States and the other small emirates located generally in Cukurova, Eastern Anatolia and Caucasus regions. The first relations of Armenians with Ottomans started in the western region of Anatolia, where Armenians were a small minority. After Bursa was made the capital city of the state by Osman Ghazi in 1324, most of the Armenians in Kutahya and the Armenian spiritual chieftain were transferred to this city. Sultan Mehmed the Conqueror, on his own initiative transferred Hovakim, the Armenian spiritual leader in Bursa, to Istanbul after he conquered Istanbul in 1453. In 1461, he had Armenian Patriarchate established as well as the Byzantine Greek Patriarchate, and he ensured Armenians to be controlled by this Patriarch. In Ottoman Empire Armenians were always treated first class citizens as the other non-Muslims were. They did not do military service, furthermore, they gained important positions in society and became rich especially by obtaining key points in commercial life. The Armenian community always lived in a tolerant and free environment, like all the other minorities and non-Muslims in the Ottoman Empire. They were not a community which was exposed to a massacre as claimed but a community who held important positions and practiced important professions in every level of state administration.
Keywords: Etnik Gruplar_Ermeniler